2019
DOI: 10.3390/ani9070456
|View full text |Cite
|
Sign up to set email alerts
|

Small Ruminants: Farmers’ Hope in a World Threatened by Water Scarcity

Abstract: The availability and sustainability of suitable and good quality drinking water is a global concern. Such uncertainties threaten livestock production with an attendant ripple effect on food security. Small ruminants, including sheep and goats, appear to be promising to smallholder farmers in solving this problem because of their ability to survive in water-limited areas and harsh environment when compared with large ruminants. Their small body size is also seen as an advantage, because less water will be requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 107 publications
2
46
0
2
Order By: Relevance
“…The observed increase in plasma glucose in this study contradicts the unchanged concentrations observed in goats (Alamer 2006;Abdelatif et al 2010), as well as the significant drop, observed in sheep (Li et al 2000) during water deprivation. Such variations in plasma glucose concentration could be as a result of the pattern of dehydration adopted in this study which allows for rehydration for 24 h. Normally, small ruminant adaptively responds to limited water intake by depressing feed intake, and such feed intake depression may affect blood concentration of glucose (Akinmoladun et al 2019). The increased blood constituents due to limited water intake agree with the report of Alamer (2006) who observed increased plasma concentrations of creatinine, urea and plasma osmolality in Saudi Arabia indigenous goats subjected to a 3-day water deprivation study.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The observed increase in plasma glucose in this study contradicts the unchanged concentrations observed in goats (Alamer 2006;Abdelatif et al 2010), as well as the significant drop, observed in sheep (Li et al 2000) during water deprivation. Such variations in plasma glucose concentration could be as a result of the pattern of dehydration adopted in this study which allows for rehydration for 24 h. Normally, small ruminant adaptively responds to limited water intake by depressing feed intake, and such feed intake depression may affect blood concentration of glucose (Akinmoladun et al 2019). The increased blood constituents due to limited water intake agree with the report of Alamer (2006) who observed increased plasma concentrations of creatinine, urea and plasma osmolality in Saudi Arabia indigenous goats subjected to a 3-day water deprivation study.…”
Section: Discussionmentioning
confidence: 95%
“…Least square means for average daily water intake and average daily feed intake from Nguni goats subjected to varying periods of water deprivation over a four-week period of successive feeding. severe water scarcity by recouping as much water as possible in the rumen during rehydration to counteract weight loss induced by water deprivation (Akinmoladun et al 2019). With an increased length of water deprivation, excessive thirst is induced leading to increased consumption of water during rehydration (Hogan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations